Real-time protection of the JET ITER-like wall based on near infrared imaging diagnostic systems. (9th August 2018) - Huber, A.; Kinna, D.; Huber, V.; Arnoux, G.; Sergienko, G.; Balboa, I.; Balorin, C.; Carman, P.; Carvalho, P.; Collins, S.; Conway, N.; McCullen, P.; et al.
Abstract: In JET with ITER-like wall (JET-ILW), the first wall was changed to metallic materials (tungsten and beryllium) [001 ] which require a reliable protection system to avoid damage of the plasma-facing components (PFCs) due to beryllium melting or cracking of tungsten owing to thermal fatigue. To address this issue, a protection system with real time control, based on imaging diagnostics, has been implemented on JET-ILW in 2011. This paper describes the design, implementation, and operation of the near infrared imaging diagnostic system of the JET-ILW plasma experiment and its integration into the existing JET-ILW protection architecture. The imaging system comprises eleven analogue CCD cameras which demonstrate a high robustness against changes of system parameters like the emissivity. The system covers about two thirds of the main chamber wall and almost half of the divertor. A real-time imaging processing unit is used to convert the raw data into surface temperatures taking into account the different emissivity for the various materials and correcting for artefacts resulting e.g. from neutron impact. Regions of interest (ROI) on the selected PFCs are analysed in real time and the maximum temperature measured for each ROI is sent to other real time systems to trigger an appropriate response of the plasma control system, depending on the location of a hot spot. A hot spot validation algorithm was successfully integrated into the real-time system and is now used to avoid false alarms caused by neutrons and dust. The design choices made for the video imaging system, the implications for the hardware components and the calibration procedure are discussed. It will be demonstrated that the video imaging protection system can work properly under harsh electromagnetic conditions as well as under neutron and gamma radiation. Examples will be shown of instances of hot spot detection that abort the plasma discharge. The limits of the protection system and the associated constraints on plasma operation are also presented. The real-time protection system has been operating routinely since 2011. During this period, less than 0.5% of the terminated discharges were aborted by a malfunction of the system. About 2%–3% of the discharges were terminated due to the detection of actual hot spots.